Acquired Cystic Kidney Disease in ESRD Patients On Maintenance Hemodialysis at A Tertiary Care Dialysis Center. (Pakistan Journal of Kidney Diseases, 2021)
Renal cysts are commonly observed in patients on maintenance hemodialysis (HD). The frequency of acquired cystic kidney disease (ACKD) is not known in our End-stage renal disease (ESRD) population.Methods: Seventy-Four ESRD patients on maintenance hemodialysis at Jinnah Hospital Dialysis center were assessed for the study.  These patients underwent ultrasound examination by consultant radiologist for the presence of renal cysts.Results:  Median duration on hemodialysis was four years (1-12 years). Cause of ESRD was Hypertension (63%) Diabetes mellitus (30%) and Obstructive uropathy (7%). Twenty-nine (40%) patients had hepatitis C infection. Sixty (85 %) patients were on thrice weekly, and 11 (15%) were on twiceweekly HD. Thirty-three (46%) patients had one renal cyst, 26 (37%) patients had 2-5 renal cysts, and 12 (17%) patients had more than five renal cysts bilaterally. Thirty-five (49%) Patients getting HD for less than three years had a median of three cysts (range 0-15), while remaining patients on HD for more than three years had a median number of 4.5 cysts (range 0-26). Nine (13%) on HD for less than one year had multiple renal cysts (1-4). None of these patients had evidence of extrarenal cysts, retroperitoneal or intrarenal hemorrhage.Conclusion: No significant correlation between ACKD and duration of hemodialysis was observed while a high frequency of renal cysts was seen earlier (within one year of HD). The reason may be the late initiation of HD at a much lower GFR, which is a routine in the developing countries .
Keywords: acquired cysctic kidney disease; kidney cysts; renal cell carcinoma; hemodialysis